Spending, utilization, and price trends for anti-obesity medications in U.S. Medicaid programs: an empirical analysis from 1999 to 2023 - Alsuhibani, Abdulrahman A.; Alrasheed, Marwan A.; Alhomoud, Ibrahim S.; Alsahali, Saud; Almalki, Ziyad S.; Guo, Jeff Jianfei (Frontiers in Medicine, 2025)
BackgroundObesity poses a significant public health and economic challenge in the United States (U.S.), with rising prevalence, particularly among individuals enrolled in Medicaid—the nation’s public health insurance program for low-income populations. Anti-obesity medications (AOMs) have become integral to managing obesity, but trends in their utilization and spending within Medicaid remain underexplored.ObjectiveTo examine Medicaid’s utilization, reimbursement, and price trends for AOMs from 1999 to 2023.MethodsA retrospective analysis assessing the utilization, reimbursement, and pricing of older and newer AOMs. Yearly prescription numbers and reimbursement were calculated for seven AOMs billed through Medicaid between 1999 and 2023. The average expenditure per prescription was used as an indicator of drug pricing.ResultsAOM prescriptions rose from 13,855 in 1999 to 938,663 in 2023, a 6,674% increase. Spending surged by over 77,805,466% due to the introduction of newer, more effective medications, including Wegovy and tirzepatide. The largest share of the market growth in 2023 was driven by these medications.ConclusionThe significant increase in AOM utilization and spending highlights the growing burden of obesity on Medicaid, emphasizing the need for policy measures to manage rising costs and ensure equitable access to treatment.